Seismic reflection profiling of the first deep geothermal field in Taiwan. (July 2018) - Shih, Ruey-Chyuan; Wang, Chien-Ying; Chen, Wen-Shan; Wang, Yin-Kai; Kuo, Hsuan-Yu; Yen, Ting-Ching; Huang, Chia-Chi; Chang, Yu-Chun; Chung, Chen-Tung; Hunag, Ming-Zi; Chang, Young-Fo
Highlights: An eastward plunging anticline containing a fault system was imaged in our study. Since the rock type was questioned, two fault structure models were proposed. The fault could be an extensional strike-slip fault or an active normal fault system. Abstract: The first deep geothermal energy development project in Taiwan was launched at the Ilan Plain in northeastern Taiwan, where metamorphic rock is covered by sediments and detailed subsurface structures were poorly known. An eastward plunging anticline containing a fault system was effectively imaged in our seismic sections. However, since some rock fragments recovered from the exploration wells were still questioned, two fault structure models were proposed. One is an extensional strike-slip fault system, and the other is an active normal fault system, which depends on whether the rock fragments were affiliated with the Hsuehshan Range or with the Backbone Range.